Pots, plates and tinpis: new income flows and the strengthening of women's gendered identities in Papua New Guinea - Koczberski, Gina (2002)
Gina Koczberski reports on the recently introduced Mama Lus Frut scheme in the oil palm smallholder sector in Papua New Guinea to remunerate women separately for their work on family-owned oil palm holdings. The scheme provides an example of the way in which women respond to new economic opportunities to redefine and strengthen their identities and relationships within the home and the wider community.